An AMOS-SEM approach to evaluating stakeholders’ influence on construction project delivery performance - AL-Fadhali, Najib (2022)
Purpose – Construction project stakeholders can have a major effect on delivering projects on time. However, little attempt has been made to address the influence of internal stakeholders on delaying project delivery. This research aims to propose the internal stakeholders’ influence as a solution to improving project delivery performance (PDP) in order to boost the value of investment in the construction industry’s projects. Design/methodology/approach – In Yemen, a structured questionnaire was distributed to owners, consultants and contractors, 283 of which were found usable after the data screening. A purposeful sampling technique was used and structural equation modelling (SEM) was adopted for analysis. The structural model was drawn up, based on seven categories of influencing factors: labour, supplier, designer, contractor, consultant, sub-contractor and owner. Findings – The results of the structural model suggest that of these seven categories, designers, owners, suppliers and subcontractors have a significant p-value and impact on PDP, while the labour and consultant’s impact was not substantiated. The findings support the proposal that internal stakeholders’ influence contributes directly to construction PDP. Originality/value – The influence of stakeholders on PDP is important. Nonetheless, few studies have focussed on their effectiveness, especially in developing countries. This paper’s contribution is evaluating the cause–effect relationship between stakeholders’ influence and construction PDP through analysis of moment structures (AMOS) analysis. The policy implications of the research are to encourage governments in general and construction companies in particular to take responsibility for improving PDP, as slow execution of construction projects leads to increased costs, failure and abandoning projects. Keywords Internal stakeholder, AMOS-SEM, Influencing factors, Project delivery performance Paper type Research paper